Analisis Implimentasi Human Capital Invesment Dalam Pengembangan Pondok Pesantren Nazhatut Thullab Prajjan Camplong Sampang - Iftihor Iftihor; Moh Holil Asy’ari; Husnul Hotimah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
The role of Islamic boarding schools in the development of society has further strengthened the existence of Islamic boarding schools, so that elements of Islamic boarding schools (kyai, congregation/students, Islamic boarding schools, and bodies or organizations under Islamic boarding schools) have exerted social, economic, political and cultural influence in fulfilling the needs of the surrounding community. The relationship between Islamic boarding schools and the community is a form of influencing and forming an open society. The focus of this research is the Analysis of the Implementation of Human Capital Investment in the Development of Nazhatut Thullab Prajjan Camplong Sampang Islamic Boarding School. The purpose of this research is to find out the process of Human Capital Investment in the development of Islamic Boarding Schools and the obstacles encountered in carrying out the Human Capital Investment. This type of research is a descriptive qualitative research. namely in various ways so that the potential and quality of existing human resources can be maximized so that the impact can be felt by the organization. One of the methods used by the Nazhhatut Thullab Prajjan Camplong Sampang Islamic Boarding School is by involving human resources in various existing training or workshops and also by providing scholarships so that they can continue to a higher level of education in accordance with the potential needed by the Nazhhatut Thullab Prajjan Camplong Sampang Islamic Boarding School and increase the wages or riwerd of existing HR. The implications of this research are that it is hoped that every organization or a particular institution can carry out Human Capital Investment because human Capital in an organization plays an important role in advancing an organization especially in the economic field of an institution.